Pemberdayaan UMKM Melalui Kegiatan Bazar di Kelurahan Tigabinanga Kecamatan Tigabinanga Kabupaten Karo - Rizki, Miladur; Syauqi, Muhammad; Nur Pramita, Juwita; Putri Mauliza Daulay, Widya; Kaloko, Nermelita; Warnisyah Harahap, Elly (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in driving local economic growth, particularly in rural areas. However, MSMEs still face various obstacles in marketing their products and developing their businesses sustainably. The Community Service Program (KKN) in Tigabinanga Village is implemented as a form of community service, aiming to empower MSMEs through bazaar activities that promote and increase the competitiveness of local products. The method of implementing the activity includes three main stages, namely: (1) the preparation stage in the form of coordination with the village government and data collection of MSMEs, (2) the implementation stage in the form of marketing strategy training, branding assistance, and holding a local product bazaar, and (3) the evaluation stage through direct observation and interviews with activity participants. The results of the activity showed that the bazaar successfully increased the visibility and sales of local products, expanded marketing networks, and enhanced the capabilities of business actors in digital promotion and product innovation. Furthermore, active collaboration between KKN students, the village government, and the community contributed to the success of the activity. In conclusion, the community service activities through the MSME bazaar in Tigabinanga had a positive impact on community economic empowerment, increased the entrepreneurial capacity of MSME actors, and strengthened the synergy between the educational world and the community in supporting sustainable local economic development.